Analisis Hasil Perkuliahan Daring Sebagai Sarana Kegiatan Pembelajaran Selama Masa Covid-19 - Rissa Megavitry (Journal on Education, 2024)
This research is development research which aims to find out whether there is a difference in the influence between the lecture process carried out online and conventionally on the learning outcomes of students at the Faculty of Engineering, UNM. The type of research used in this research is descriptive quantitative research. The descriptive quantitative research carried out aimed to describe the learning outcomes of UNM Faculty of Engineering students conducted online and face-to-face during the COVID-19 pandemic at the UNM Faculty of Engineering. The data used in this research is 600 primary data, namely data taken directly during the research using appropriate research instruments. Data in the form of social studies students from the Faculty of Engineering. The data collection technique used is the Purposive Sampling Technique. The inferential statistical data analysis used in this research is the paired T-test. Analysis was carried out after ensuring that the data held was normally distributed data. Based on the results of the research and discussion that have been described and looking at the problems from the problem formulation, it can be concluded that with the Sig. is 0.000, which is a value smaller than 0.05. Thus, H0 is rejected and H1 is accepted. So it can be concluded that there is an average difference between social studies students at the Faculty of Engineering, Makassar State University in conventional and online lectures.